Total Thyroidectomy for Benign Thyroid Diseases: What is the Price to be Paid? - Gangappa, Rajashekara Babu (J Clin Diagn Res, 2016)
INTRODUCTION: Total thyroidectomy has been used to treat patients with malignant thyroid disease. But for patients with benign thyroid disease, the safety and efficacy of total thyroidectomy is a matter of debate. Subtotal thyroidectomy that was previously the treatment of choice for benign thyroid disease has been associated with high recurrence rates. The risk of permanent complications is greatly increased in patients who undergo surgery for recurrence of benign thyroid disease. Total thyroidectomy is an operation that can be safely performed, with low incidence of permanent complications, which allows one to broaden its indications in various benign thyroid diseases, thus avoiding future recurrences and reoperations. AIM: To assess the benefits of total thyroidectomy for benign thyroid diseases. MATERIALS AND METHODS: This randomized prospective study was conducted between Feb 2013 and Nov 2014 in the Department of General Surgery at Bangalore Medical College and Research Institute. It included 116 patients undergoing total thyroidectomy procedure for benign thyroid disease. All cases were followed-up for a period of 6 months for incidence of RLN palsy, hypoparathyroidism, disease recurrence and number of incidental malignancies detected on postoperative histological analyses of the thyroid specimens. RESULTS: Most of the patients were in the third decade of their lives. The female to male ratio was 6.7:1. Total thyroidectomy was done for 116 benign thyroid diseases with multinodular goiter as the most common diagnosis. The incidence of postoperative hypocalcaemia was 16.37% (however, only 1 patient developed permanent hypocalcaemia) and that of wound infection was 2.58% and seroma formation was 2.58%. None of the patients included in this study had haematoma formation or RLN paralysis. An incidental malignancy was identified in 11.20% patients. CONCLUSION: Total thyroidectomy shows benefits in eradicating multinodular goiter, alleviating Grave’s opthalmopathy, treating Hashimoto’s thyroiditis and preventing recurrence. It decreases the likelihood of future operations for recurrent disease or completion thyroidectomy for incidental thyroid cancer thus decreasing the associated risks of increased morbidity associated with second operation. Therefore, for benign thyroid diseases requiring surgical management total thyroidectomy can be considered the treatment of choice.